Influência da localização de instalações logísticas na Região Metropolitana de Belo Horizonte - Odirley Rocha dos Santos (2017)
Logistic sprawl is a phenomena associated with the urban expansion (urban sprawl). It is defined as the historical trend of the geographic expansion of the logistics facilities within a metropolitan area. Freight transportation planning must be aligned with urban planning and sustainable mobility of a region. In order to create this synergy, it is necessary to provide solutions to reduce the logistics sprawl. Hence, for the urban planning standpoint, keeping the logistics facilities close to the transport infrastructure, as well as close to the destination of the goods is crucial to economic sustainability of the region. This dissertation addresses an investigation of the logistics sprawl in Belo Horizonte Metropolitan Area and vicinity of municipalities for the period 1995-2015. Applying secondary data, acquired from the Board of Trade of the State of Minas Gerais (JUCEMG), the methodology of classification of logistics facilities was adapted to Brazil. This study investigates the magnitude of logistics sprawl in the BHMA, comparing it with the patterns of this phenomena in Europe, North America and Japan. The study used GIS approaches for geolocating the logistics facilities, hence calculating the mean (or gravity) center of these infrastructures and analyzing the geographic shifting and expansion in the period. Results revealed a sizable rise in the number of logistics facilities with a small logistics sprawl. The results also exposed the characteristics of the warehouses in the area studied and, therefore, the evaluation of the impact of public policies for land use and land cover in urban/regional freight, along with the analysis of its relationship with demographic and economic data, road system, urban planning and mobility of the region.